Effects of melatonin on adult human mesenchymal stem cells in osteoblastic differentiation. An experimental in vitro study - J. L. Calvo-Guirado; C. PÉREZ-ALBACETE; C. Pérez Sánchez; A. Boquete-Castro; J. E. Maté-Sánchez de Val; J. E. Delgado Peña; M.P. RAMÍREZ FERNÁNDEZ; M. Garcés; L. Meseguer-Olmo; G. Gómez Moreno (Ariesdue, 2015)
Aim The purpose of this study was to determine if different melatonin concentrations enhances human adult mesenchymal stem cells (MSCs) differentiation into osteoblasts, in comparison with MSCs cultured with dexamethasone (DEX). Material and Methods MSCs were treated with different melatonin concentrations. Specifically: Group I: untreated MSCs; Group II: MSCs exposed to physiological doses of melatonin of 0.01 µM; Group III: MSCs exposed to 50 µM melatonin; Group IV: MSCs exposed to 100 µM melatonin; Group V: MSCs exposed to 150 µM melatonin; Group VI: MSCs exposed to 100 µM of DEX. Cell viability, adhesion, growth, differentiation and activity were evaluated at different time points (3, 7, 14, 21 and 28 days) using the following assays MTT, SEM, Flowcytometry, ALP activity, Alizarin Red staining and RT-PCR. Results Melatonin stimulated the viability and alizarin red activity of MSCs in a dose-dependent manner. Melatonin 50 µM significantly increased ALP activity, especially after 21 and 28 days of culture. A significant decrease in the expression of membrane markers CD75, CD105 and CD90 was recorded over time, in the presence of melatonin; therefore, the MSCs were early differentiated into osteoblasts regardless of the melatonin concentration. Conclusion These results demonstrated that melatonin directly accelerated the differentiation of human stem cells into osteoblasts and also suggested that melatonin could be applied as a pharmaceutical agent to promote bone regeneration.